Sodium Balance During Extra Corporeal Dialysis - Locatelli Francesco; Colzani Sara; D′Amico Marco; Manzoni Celestina; Di Filippo Salvatore (Saudi Journal of Kidney Diseases and Transplantation, 2001)
In order to reduce intradialytic and interdialytic morbidity, it is important to obtain a zero sodium balance at the end of each dialysis session. This can be achieved by matching exactly the interdialytic sodium and water intake with the intradialytic sodium and water removal. A positive sodium balance can be obtained by using hypernatric dialysis or "sodium ramping" or convective techniques. While reducing the intradialytic side effects (hypotension, cramps, nausea, vomiting), these methods may increase the interdialytic side effects (thirst, weight gain, hypertension and pulmonary edema). Given the highly variable amounts of sodium introduced during the interdialytic periods, the use of sodium-conductivity kinetic models allows removing exactly the amount of sodium accumulated in the interdialytic period. This strategy may be advantageous towards cardiovascular stability in patients prone to dialysis hypotension.